Violation of the assumption of homoscedasticity and detection of heteroscedasticity - Đalić, Irena; Terzić, Svetlana (Decision Making: Applications in Management and Engineering, 2021)
In this paper, it is assumed that there is a violation of homoskedasticity in a certain classical linear regression model, and we have checked this with certain methods. Model refers to the dependence of savings on income. Proof of the hypothesis was performed by data simulation. The aim of this paper is to develop a methodology for testing a certain model for the presence of heteroskedasticity. We used the graphical method in combination with 4 tests (Goldfeld-Quantum, Glejser, White and Breusch-Pagan). The methodology that was used in this paper showed that the assumption of homoskedasticity was violated and it showed existence of heteroskedasticity.